Sinpatju enterprise : t-shirt folding machine / Muhamad Azri Hanif Mohd Aziz ... [et al.] - Mohd Aziz, Muhamad Azri Hanif; Mohamed Amin, Muhammad; Ahmad Fairul Fauzi, Ahmad Amiierul Firdaus; Jamlludin, Hidayatul Fairuz; Nasir, Masmira (2015)
Entrepreneurship is a process innovation and new venture creation through four dimensions which includes individuals, organization, environment and institution. In order to form a business, there are quiet numbers of phase that should be understood and develops by entrepreneur. SINPAT JU is a partnership company ventured by five partners which is three male and two female. The business capital is amounted to RM 26,500 where the total contribution of each member is RM 5,300 and the rest RM 37,308 is from bank's loan. Each partner will hold different and important position in the company such as General Manager, Administration Manager, Operation Manager, Marketing Manager and Financial Manager. T-shirt Folding Machine is the product name of our company and our product only takes three steps to fold and can reduce human energy yet save folding time. SINPAT JU offers new, innovative, and simple yet portable product that can be used by all type of consumer. Our company location is at No. 24 Jalan Lembah 19, Jalan Persiaran Bandar Seri Alam, 81750 Bandar Seri Alam, Johor. SINPAT JU will be operating for six days a week (Sunday - Friday) at 8am until 6pm.